Symposium : mental health and the sustainable development goals - Dybdahl, Ragnhild (Đại học Quốc gia Hà Nội, 2020)
In 2015. all United Nations Member States adopted the agenda for sustainable all United Nations Member States adopted the agenda for sustainable development and agreed on 17 goals to be reached by 2030. This is a global commitment to partnerships to tackle climate change and environmental challenges ; to end poverty ; promote equality , justice and peace , and improve health and education . This symposium brings together different perspectives on why mental health is important to reach the sustainable development goals ( SDGs ) , and how to strengthen mental health in ways that contribute to the SDG agenda . Mental health challenges are important barriers to reach the SDGs . For example , psychological consequences of political / interpersonal violence and poverty impact human and economic development . Poor mental health threatens many of the SDGs . Good mental health on the other hand , is a vital contribution to reach all SDGs , e.g. through increased social capital , increased productivity , and reduced vulnerability to environmental disasters . The symposium explores the role of human rights and ethics , early childhood development , psychological trauma interventions , and capacity building for mental health through university cooperation